Radiografi Oesophagus dengan Sangkaan Striktur Oesophagus Di Rumah Sakit Umum Haji Medan - Tambunan, Justinus; Nuryatno, Nuryatno (Poltekkes Kemenkes Kendari, 2023)
The esophagus (esophagus) is a muscular tube-shaped channel 20-25 cm long, starting from the pharynx to the cardiac entrance to the stomach. Located behind the trachea and in front of the spine. After passing through the thoracic cavity, it penetrates the aphragm, then enters the abdomen and connects to the stomach. Radiographic examination of the esophagus is a radiographic examination using positive and negative contrast media to reveal the anatomy, function and abnormalities that occur in the esophagus. To get this diagnostic picture, a radiological examination is carried out using X-rays. With the help of X-rays we can find out if there are abnormalities in the esophagus and changes in its structure and its effect on the surrounding organs. The projections carried out include Antero Posterior Projection using contrast media, and Lateral Projection. This research uses descriptive and qualitative research methods. The research was carried out in February 2022 at the Radiology Installation at the Haji General Hospital in Medan using a General Pur-pose X-Ray (GPX) X-ray aircraft with a capacity of 500mA, and using a shadow recording process with Computer Radiography (CR). Data collection techniques include observation, documentation and interviews. Then the collected data is processed and connect